Adolescent Girls' Weight-Related Family Environments, Minnesota - Katherine W. Bauer, PhD, MS; Dianne Neumark-Sztainer, PhD, MPH, RD; Jayne A. Fulkerson, PhD; Mary Story, PhD, RD (Centers for Disease Control and Prevention, 2011)
Significant sociodemographic disparities exist in the prevalence of obesity among adolescent girls, and in girls' participation in physical activity, sedentary activity, and healthful dietary intake. However, little is known of how factors in the family environment associated with weight and behavior vary by sociodemographic groups. We examined differences and similarities in the weight-related family environments of adolescent girls by race/ethnicity, parental educational attainment, and US nativity. Data are from the baseline assessment of 253 parent/daughter dyads. Parents completed survey items on the family environment; parents and girls reported their sociodemographic characteristics. Hierarchical regression models were used to test relationships between the family environment and sociodemographic characteristics. Parents of Asian girls reported qualities supportive of physical activity and healthy eating. Higher parental education was associated with more parental modeling of and support for physical activity and greater frequency of family meals. Parents of foreign-born girls reported having fewer televisions in the home, more frequent family meals, and fewer fast-food family meals. Understanding sociodemographic differences in the family environments of adolescent girls can inform the development of obesity prevention programs and reduce disparities in adolescents' weight status, physical activity, sedentary behavior, and healthful dietary intake.